2020
DOI: 10.3991/ijet.v15i22.17075
|View full text |Cite
|
Sign up to set email alerts
|

How Do Students Behave When Using A Tutoring System? Employing Data Mining to Identify Behavioral Patterns Associated to The Learning of Mathematics

Abstract: The inclusion of technology in the academic processes has led to constant innovation and investment of resources to offer a first-level educational service, with international standards, methodologies, study plans, and last generation laboratories. This paper focuses on how teachers can make use of an educational technology tool that will allow them to identify patterns that are associated with learning based on human-computer interaction. We present evidence of learning outcomes based on the detection of beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is concluded that learners' implicit and intrinsic characteristics cannot be directly observed and measured, but they can be excavated and perceived through massive data of online learning behavior [46], so as to implement corresponding interventions to promote effective learning or better teaching. Moreover, video in SPOC courses is a preferred form of learning for students to acquire knowledge [52, 65].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is concluded that learners' implicit and intrinsic characteristics cannot be directly observed and measured, but they can be excavated and perceived through massive data of online learning behavior [46], so as to implement corresponding interventions to promote effective learning or better teaching. Moreover, video in SPOC courses is a preferred form of learning for students to acquire knowledge [52, 65].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Logs of student-computer interaction are a primary source of educational data mining [24]. The web mining methods outlined by Romero and Ventura are widely used in EDM today, both in the mining of web data and other educational data.…”
Section: Classification Clustering and Outlier Detection Association ...mentioning
confidence: 99%
“…So if engineering education students graduate on time, it will help improve the quality of a university. On the other hand, engineering education students will be helped and reduce the burden of spending on tuition fees (Melendez-Armenta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%